A Microfluidic Multisize Spheroid Array for Multiparametric Screening of Anticancer Drugs and Blood–Brain Barrier Transport Properties. Issue 11 (24th March 2021) - Eilenberger, Christoph; Rothbauer, Mario; Selinger, Florian; Gerhartl, Anna; Jordan, Christian; Harasek, Michael; Schädl, Barbara; Grillari, Johannes; Weghuber, Julian; Neuhaus, Winfried; Küpcü, Seta; Ertl, Peter
Abstract: Physiological‐relevant in vitro tissue models with their promise of better predictability have the potential to improve drug screening outcomes in preclinical studies. Despite the advances of spheroid models in pharmaceutical screening applications, variations in spheroid size and consequential altered cell responses often lead to nonreproducible and unpredictable results. Here, a microfluidic multisize spheroid array is established and characterized using liver, lung, colon, and skin cells as well as a triple‐culture model of the blood‐brain barrier (BBB) to assess the effects of spheroid size on (a) anticancer drug toxicity and (b) compound penetration across an advanced BBB model. The reproducible on‐chip generation of 360 spheroids of five dimensions on a well‐plate format using an integrated microlens technology is demonstrated. While spheroid size‐related IC50 values vary up to 160% using the anticancer drugs cisplatin (CIS) or doxorubicin (DOX), reduced CIS:DOX drug dose combinations eliminate all lung microtumors independent of their sizes. A further application includes optimizing cell seeding ratios and size‐dependent compound uptake studies in a perfused BBB model. Generally, smaller BBB‐spheroids reveal an 80% higher compound penetration than larger spheroids while verifying the BBB opening effect of mannitol and a spheroid size‐related modulation on paracellular transport properties. Abstract : A microfluidic platform is presented that builds on the advancement of a spheroid‐on‐a‐chip technology that accommodates 360 spheroids of five different dimensions on a microtiter plate format supporting a range of human tissue models. Thus, this platform closes an essential technological gap, enabling rapid and easy production of spheroids of defined sizes for pharmaceutical screening in a standardized and reproducible manner.